Human biomonitoring initiative (HBM4EU): Human biomonitoring guidance values (HBM-GVs) derived for bisphenol A. (September 2021) - Ougier, Eva; Zeman, Florence; Antignac, Jean-Philippe; Rousselle, Christophe; Lange, Rosa; Kolossa-Gehring, Marike; Apel, Petra
Highlights: HBM-GVs of 230 µg/L and 135 µg/L urinary total BPA derived for adults and children from the general population, respectively. Allow the interpretation of total urinary BPA concentrations measured in 24-hour or spot-urine samples collected at random times of the day in large-scale studies. HBM-GVs according to the relative contribution of both the oral and dermal routes to the global BPA exposure also discussed. No HBM-GV for urinary total BPA proposed for interpreting HBM results of occupationally exposed adults. Abstract: The "European Human Biomonitoring Initiative" (HBM4EU) derives human biomonitoring guidance values (HBM-GVs) for the general population (HBM-GVGenPop ) and/or for occupationally exposed adults (HBM-GVWorker ) for several priority substances and substance groups as identified by policy makers, scientists and stakeholders at EU and national level, including bisphenol A (BPA). Human exposure to BPA is widespread and of particular concern because of its known endocrine-disrupting properties. Unlike the conjugated forms of BPA circulating in the body, free BPA is known to interact with the nuclear estrogen receptors. Because free BPA is considered to be more toxicologically active than the conjugated forms (e.g. BPA-glucuronide (BPA-G) and BPA-sulfate (BPA-S)), its measurement in blood provides the superior surrogate of the biologically effective dose. However, considering the difficulty of implementing blood sampling in large HBM cohorts, as well as the current analytical capacities complying with the quality assurance (QA)/quality control (QC) schemes, total BPA in urine (i.e. the sum of free and conjugated forms of BPA measured after an hydrolysis of phase II metabolites) was retained as the relevant exposure biomarker for BPA. HBM-GVGenPop for total BPA in urine of 230 µg/L and 135 µg/L for adults and children, respectively, were developed on the basis of toxicological data. To derive these values, the concentrations of urinary total BPA consistent with a steady-state exposure to the temporary Tolerable Daily Intake (t-TDI) of 4 µg/kg bw/day set in 2015 by the European Food Safety Authority (EFSA) were estimated. The BPA human physiologically-based pharmacokinetic (PBPK) model developed by Karrer et al. (2018) was used, assuming an oral exposure to BPA at the t-TDI level averaged over 24 h. Dermal uptake of BPA is suspected to contribute substantially to the total BPA body burden, which in comparison with the oral route, is generating a higher ratio of free BPA to total BPA in blood. Therefore, an alternative approach for calculating the HBM-GVGenPop according to the estimated relative contributions of both the oral and dermal routes to the global BPA exposure is also discussed. Regarding BPA exposure at the workplace, the steady-state concentration of urinary total BPA was estimated after a dermal uptake of BPA that would generate the same concentration of free BPA in plasma (considered as the bioactive form) as would a 24 h-averaged intake to the European Chemicals Agency (ECHA)'s oral DNEL of 8 µg BPA/kg bw/day set for workers. The predicted concentration of urinary total BPA at steady-state is equivalent to, or exceeds the 95th percentile of total BPA in urine measured in different European HBM studies conducted in the general population. Thus, no HBM-GVWorker was proposed, as the high background level of BPA coming from environmental exposure - mostly through food intake - is making the discrimination with the occupational exposure to BPA difficult.